Cell‐of‐origin classification by gene expression and MYC‐rearrangements in diffuse large B‐cell lymphoma of children and adolescents. (23rd June 2017) - Szczepanowski, Monika; Lange, Jonas; Kohler, Christian W.; Masque‐Soler, Neus; Zimmermann, Martin; Aukema, Sietse M.; Altenbuchinger, Michael; Rehberg, Thorsten; Mahn, Friederike; Siebert, Reiner; Spang, Rainer; Burkhardt, Birgit; et al.
Summary: We present the largest series of diffuse large B‐cell lymphoma (DLBCL) in patients younger than 18 years analysed to date by gene expression profiling using Nanostring technology to identify molecular subtypes and fluorescent in situ hybridization for translocations of MYC . We show that the activated B cell‐like subtype of DLBCL is exceedingly rare in children and – in contrast to adults‐ not associated with outcome. Furthermore, we review the current literature and demonstrate that MYC translocations are not more frequent in paediatric compared to adult DLBCL. A prognostic role of MYC in the paediatric age groups seems unlikely.